Oracle user productivity kit 3.5: build high-quality training simulations using Oracle UPK 3.5 - Manuel, Dirk (Community experience distilled, 2009)
In Detail As the complexity of software applications increases and the length of the implementation life cycles decreases, companies are looking for effective ways of training users in new applications, and the new releases of existing applications. Oracle's User Productivity Kit solves these problems by enabling the rapid creation of software application simulations, which are used for training purposes or to generate business documents. Although UPK provides such advanced features, nothing has been written about this application yet. This book provides a guided approach to building high-quality, re-functional simulations of tasks performed in software applications. With this book in hand, it is easy for organizations that are implementing or upgrading software to meet their full training and documentation requirements. This book explains how to harness all of the functionality provided by Oracle's User Productivity Kit, formerly known as OnDemand, to develop better quality training. It also covers the advanced topics of customizing UPK's built-in delivery formats, and defining new ones to extend the capabilities of UPK. This book explains how to make the most of Oracle User Productivity Kit's available functionality to create high-quality simulations. These simulations can be used during instructor-led training, self-directed learning, or refresher training. By following the approach described in this book, you will create world-class training material that your trainees will find useful, engaging, and informative. As a result, they will remember more of what they are taught, and will be better equipped to use the application on which you are training them. In turn, they will become more productive sooner, make fewer mistakes, and require less support. To ensure effective knowledge transfer through training simulations, it is necessary to add a business context to recordings, and to provide additional explanations. This book will teach you more than simple mouse-clicks and keystrokes. A guided approach to creating interactive training simulations and performance-support documentation. Customer Review "...The book would certainly have saved me thousands of pounds, as it uses real-world ERP examples that we can all relate to. With it, we could have worked through the examples portrayed across the book's 500 pages to create impressive training simulations. Without it, my team learned by trial and error on Oracle 11.5.10r2 at Sandwell MBC." Read the full review here. Approach This book provides a practical tutorial on UPK's functionality, with the aim of teaching developers how to best leverage this functionality to develop high-quality training material. The book guides readers from the basics of recording through to adding value through Web Pages Packages (Infoblocks), Role filters, Glossaries, and more. The book starts with the recording of a simple simulation, and builds on this recording throughout, by introducing new UPK features and incorporating the lessons learned into this recording. Interwoven into this, the key tasks (how-tos) are formatted in such a way that they can be quickly identified and referred to, making this book useful as an ongoing reference to UPK functionality. Who this book is for This book has been written primarily for new or intermediate training developers who will be using Oracle UPK or OnDemand to create their training material. If you are an experienced UPK developer who wants to tailor UPK to meet your own, specific requirements, you will love this book.